Benthic N2 fixation in coral reefs and the potential effects of human‐induced environmental change. Issue 9 (31st March 2014) - Cardini, Ulisse; Bednarz, Vanessa N.; Foster, Rachel A.; Wild, Christian
Abstract Tropical coral reefs are among the most productive and diverse ecosystems, despite being surrounded by ocean waters where nutrients are in short supply. Benthic dinitrogen (N2) fixation is a significant internal source of "new" nitrogen (N) in reef ecosystems, but related information appears to be sparse. Here, we review the current state (and gaps) of knowledge on N2 fixation associated with coral reef organisms and their ecosystems. By summarizing the existing literature, we show that benthic N2 fixation is an omnipresent process in tropical reef environments. Highest N2 fixation rates are detected in reef‐associated cyanobacterial mats and sea grass meadows, clearly showing the significance of these functional groups, if present, to the input of new N in reef ecosystems. Nonetheless, key benthic organisms such as hard corals also importantly contribute to benthic N2 fixation in the reef. Given the usually high coral coverage of healthy reef systems, these results indicate that benthic symbiotic associations may be more important than previously thought. In fact, mutualisms between carbon (C) and N2 fixers have likely evolved that may enable reef communities to mitigate N limitation. We then explore the potential effects of the increasing human interferences on the process of benthic reef N2 fixation via changes in diazotrophic populations, enzymatic activities, or availability of benthic substrates favorable to these microorganisms. Current knowledge indicates positive effects of ocean acidification, warming, and deoxygenation and negative effects of increased ultraviolet radiation on the amount of N fixed in coral reefs. Eutrophication may either boost or suppress N2 fixation, depending on the nutrient becoming limiting. As N2 fixation appears to play a fundamental role in nutrient‐limited reef ecosystems, these assumptions need to be expanded and confirmed by future research efforts addressing the knowledge gaps identified in this review.